Композиційні кластерні структури мобільних генетичних елементів у інтронах гена MGMT як джерело регуляторних послідовностей - Підпала, О.В.; Лукаш, Л.Л. (Фактори експериментальної еволюції організмів, 2014)
Aims. It was carried out analysis of the composite cluster structures MGE in intron 2 and 3 of human MGMT gene for the sequences homologous to binding sites of transcription factors. Methods. Searching and identifying MGE was realised by using CENSOR (http://www.girinst.org). Functional sites were defined by program TFSEARCH: Searching Transcription Factor Binding Sites (ver 1.3) (http://www.cbrc.jp/research/db/TFSEARCH.html). Results. Composite clusteres in the introns 2 and 3 of human MGMT gene consist of Alu-repeat and fragments of LINE-elements. Both sequences are enriched promotorspecific elements including the TATA box, AP-1, Sp1, SREBP-1, Oct-1, HSF2 and others. Exept that fragments of the LINE-elements have sites binding for the glucocorticoid receptor and orphan hormone nuclear receptor. Conclusions. The obtained results allow to consider analyzed intron clusters of MGE as potential alternative promoters.

Key words: human О⁶-methylguanin-DNA methyltransferase gene, mobile genetic elements, composite cluster structures.